Public Sector Reforms and Financial Transparency:Experiences from Indonesia Districts (Public Sectir Reforms and Financial Transparency_Contemporary Southeast Asia095) - Purwanto, Erwan Agus (Public Sector Reforms and Financial Transparency:Experiences from Indonesia Districts, 2009)
As in mony Asian , Africon,and Lion Amirican Conuntres democratization end devolution reforem have characterized the recent development of public management in indonesia, this article analyses the current develoment of "good governance" in indonesia local goverrnment, the main objectiove is to assess the level of transparency ,the mechanisms for hiding and the extent of corruption in district budgeting and accounting . the empirical data consists of200 in depth interviews with members of the executive. legislative and civil society institutions , the article concludes that national systems and traditions of politics and bureaucracy have a strong negative impact on local administrative procedures leaving only marginal space for regional